2021
DOI: 10.1007/s11523-021-00837-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Treatment Switching on Overall Survival from the PROfound Study in Homologous Recombination Repair (HRR)-Mutated Metastatic Castration-Resistant Prostate Cancer (mCRPC)

Abstract: Background In oncology trials, treatment switching from the comparator to the experimental regimen is often allowed but may lead to underestimating overall survival (OS) of an experimental therapy. Objective This study evaluates the impact of treatment switching from control to olaparib on OS using the final survival data from the PROfound study and compares validated adjustment methods to estimate the magnitude of OS benefit with olaparib. Patients and methods The primary population from PROfound (Cohort A) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…For decades, cancer genomists have struggled to identify gene biomarkers whose altered sequence (e.g., Reference [1]) or/and expression (e.g., Reference [2]) is/are indicative for the prostate cancer (PCa) and could serve in active surveillance [3] of PCa development. The skillful handling of biomarkers was hoped to increase the survival rate (e.g., Reference [4]), destroy the cancer cells (e.g., Reference [5]) and reduce their proliferation (e.g., Reference [6]) and spreading (e.g., Reference [7]). Biomarkers' "smart" manipulation was also thought to block the PCa recurrence after various types of treatments (e.g., References [8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, cancer genomists have struggled to identify gene biomarkers whose altered sequence (e.g., Reference [1]) or/and expression (e.g., Reference [2]) is/are indicative for the prostate cancer (PCa) and could serve in active surveillance [3] of PCa development. The skillful handling of biomarkers was hoped to increase the survival rate (e.g., Reference [4]), destroy the cancer cells (e.g., Reference [5]) and reduce their proliferation (e.g., Reference [6]) and spreading (e.g., Reference [7]). Biomarkers' "smart" manipulation was also thought to block the PCa recurrence after various types of treatments (e.g., References [8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses using RPSFTMs, a method used to adjust for crossover, showed that the HR for olaparib versus control was between 0.27 (95% CI, 0.19 to 0.75) and 0.40 (95% CI, 0.27 to 0.90), depending on the model selected (Appendix Fig A3A without recensoring, and Fig A3B with recensoring). 23…”
Section: Resultsmentioning
confidence: 99%
“…HR, hazard ratio; HRR, homologous recombination repair; rPFS, radiographic progression-free survival.
FIG A3.Kaplan-Meier curves for OS in patients with a BRCA alteration, adjusted for treatment switching using RPSFTM (combined including co-occurring alterations). 23 From Evans R et al: Exploring the impact of treatment switching on overall survival from the PROfound study in homologous recombination repair (HRR)-mutated metastatic castration-resistant prostate cancer (mCRPC), Targeted Oncology 16:613–23. Copyright © 2021, Springer Nature.
…”
Section: Brca Alterationsmentioning
confidence: 99%
“…7 Recently, poly-ADP ribose polymerase inhibitors (PARPis) have been approved for the treatment of metastatic prostate cancer carrying HRR gene mutations. 8 Furthermore, HRR gene mutations are rendered sensitive to chemotherapy and immunotherapy. 9,10 Nonetheless, the molecular mechanisms and tumor immune profiles of HRR genes and their relevance to the response to clinical therapy in UTUC remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination repair (HRR) participates in DNA repair mechanisms, which might contribute to the reorganization of chromosomes, genome instability, and cell apoptosis 7 . Recently, poly‐ADP ribose polymerase inhibitors (PARPis) have been approved for the treatment of metastatic prostate cancer carrying HRR gene mutations 8 . Furthermore, HRR gene mutations are rendered sensitive to chemotherapy and immunotherapy 9,10 .…”
Section: Introductionmentioning
confidence: 99%